Childhood poverty and school readiness: Differences by poverty type and immigration background - Randip Gill; Mohammad Ehsanul Karim; Joseph H. Puyat; Martin Guhn; Magdalena Janus; Monique Gagné Petteni; Barry Forer; Anne M. Gadermann (SSM: Population Health, 2024)
Objectives: Poverty exposes children to adverse conditions that negatively impact development. However, there is limited understanding on how different types of poverty may affect children of various immigration backgrounds differently in outcomes such as school readiness. This study examined these relationships between household and/or neighbourhood poverty, poverty timing, and immigration background with school readiness outcomes at kindergarten. Methods: This study utilized a retrospective, population-based cohort of administrative records linked with surveys completed by kindergarten teachers for 15 369 children born in British Columbia, Canada. The exposures investigated were neighbourhood poverty (residing in a neighbourhood in the lowest income-quintile) and/or household poverty (receiving a health insurance subsidy due to low household income). Experiencing both neighbourhood and household poverty simultaneously was defined as “combined” household and neighbourhood poverty. The outcome of vulnerability on school readiness domains was assessed at kindergarten (47.8% female; mean age = 6.01 years) using teacher ratings on the Early Development Instrument (EDI). Results: Children exposed to combined poverty between age 0 and 2 had greater odds of being vulnerable in two or more domains of school readiness than children not exposed to any poverty during this period (adjusted odds ratio (aOR) = 2.07, 95% CI: [1.74; 2.47], p < 0.001). The effect of combined poverty was larger than household poverty only (aOR = 1.54, 95% CI: [1.31; 1.82], p < 0.001) or neighbourhood poverty only (aOR = 1.49, 95% CI: [1.30; 1.70], p < 0.001). Combined poverty was associated with negative outcomes regardless of timing. Both non-immigrants (aOR = 2.40, 95% CI: [1.92; 3.00], p < 0.001) and second-generation immigrants (aOR = 1.63, 95% CI: [1.22; 2.17], p < 0.001) experiencing combined poverty scored lower on school readiness. Conclusions: Children who experienced combined poverty had lower levels of school readiness at kindergarten, regardless of timing and immigration background.